The Experience of Nursing Professors and Students about the Objective Structured Clinical Examination - Pouya Nematzad; Parand Pourghane; Fereshteh Besharati; Seyed Mohammad Sadegh Mozafari (Kerman University of Medical Sciences, 2023)
Background: Clinical evaluation in medical sciences is one of the important components of education. One of these evaluations is the clinical assessment for final-year nursing students when they are going to graduate and start their profession. To this end, this study aimed to explore the experiences of nursing professors and students regarding the Objective Structured Clinical Examination (OSCE).Methods: This qualitative study was conducted using a content analysis approach on 7 nursing professors and 21 nursing students who completed OSCE in 2019 at the Nursing and Midwifery School of Guilan University of Medical Sciences in northern Iran. The participants were selected using purposive sampling and the data were collected through semi-structured individual interviews. The collected data were analyzed using the content analysis approach proposed by Graneheim and Lundman. The credibility of the findings was checked using the criteria proposed by Guba and Lincoln.Results: The data analysis revealed 3 main categories and 10 subcategories: OSCE as a highly efficient test(the requirement for reviewing the courses, student benchmarking, and randomly arranged questions), OSCE challenges (the low assessment ability of the test, the influence of the nursing instructor's prior knowledge, and having little practical experience), the solutions to improve OSCE (diversification of evaluation techniques, shortening the distance between theory and practice, the effectiveness of the OSCE scores for graduation, and the application of stress reduction methods).Conclusion: Despite some problems such as its stressful nature and its unknown format for students, OSCE seems to be effective for the clinical assessment of students before their graduation. Taking advantage of the professors' and students' perspectives can eliminate or reduce the problems and improve the positive points for planning and conducting the OSCE in the future.